Chemical Composition and fermentative characteristics of Elephant grass (Pennisetum purpureum Schum.) silages added of increasing levels of mango (Mangifera indica L.) byproducts - Sa, Cynthia Renata Lima; Neiva, Jose Neuman Miranda; Goncalves, Josemir de Souza [UNESP]; Cavalcante, Maria Andrea Borges; Lobo, Raimundo Nonato Braga (Univ Federal Ceara, 2007)
Aiming at evaluating the use of those byproducts on ruminant feeding an experiment has been carried out in the Forage Research department (www.npf.ufc.br), in order to evaluate the effects of addition of increasing levels of mango processing byproducts (MB) in Elephant grass silages. Twenty experimental silos made of PVC pipe (100 x 340 mm), in a completely randomized design with 5 levels of addition (0; 5; 10; 15; and 20%) of MB and 4 replications. Upon 32 days of ensilage, samples were collected for determination of levels of dry Matter (DM), crude protein (CP), ethereal extract (EE), neutral detergent fiber (NDF), acid detergent fiber (ADF), hemicelluloses (HC), ammonia nitrogen (N-NH3), and pH values. Data were evaluated by analyses of variance and regression analyses using the F test at the 5% level. The levels of DM and CP increased of 0.50 and 0.03 percentage units, respectively, for every 1% of MB added. The levels of NDF and ADF decreased of 0.51 and 0.24 percentage units, respectively, for every 1% of MB added. The levels of N-NH3 decreased from 4 to 23 percentage units while pH values remained constant (p>0.05), with average values of 3.29. Addition of 20% of MB improved silages chemical composition by promoting an increase in the levels of MS and reduction in the levels of fiber.
Keywords: additive; ammonia nitrogen; ensilage; fermentation; pH